(untitled) (Journal of Environmental Science and Natural Resources, 2016)
A pot experiment was conducted at Soil Science Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, during January to April 2014 to investigate the growth, abscission of flower and pod and yield performance of three soybean varieties (BINA Soybean-1, BINA Soybean-2, and Shohag) under three different temperature conditions. Flower abscission number and percentage were maximum in elevated temperature but the abscission of pods plant-1 was found to be the maximum in ambient temperature. In case of the performance of varieties, tallest plant and maximum node plant-1 were noted from the variety Shohag but number of nodules plant-1 , number of seeds pod-1, weight of 100 seed and seed yield was highest in BINA soybean2 while BINA soybean1 had maximum flowers plant-1 and pods plant-1. Abscission of flowers plant-1 was maximum in BINA soybean1 under elevated temperature while similar variety grown under ambient temperature obtained the maximum abscission of pods plant-1 and the variety Shohag grown under elevated temperature noted the maximum abscission percentage of flower at all the data recording stages. These results suggested that ambient temperature and BINA soybean2 singly or their interaction would be the most significant compared to others. J. Environ. Sci. & Natural Resources, 8(2): 89-92 2015